On some imbedding relations between certain sequence spaces - Mursaleen, M.; Noman, A. K. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
In the present paper, we introduce the sequence space $l^{λ}_p$ of non-absolute type which is a $p$-normed space and a $BK$-space in the cases of $0 < p < 1$ and $0 < p < 1$ i $1 ≤ p < ∞$, respectively. Further, we derive some imbedding relations and construct the basis for the space $l^{λ}_p$, where $1 ≤ p < ∞$.